Mãos que falam, fios que educam: história e memória da cultura da renda de bilro em Ilha Grande do Piauí - Silva, Rozeli Costa (2024)
This research will deal with aspects of the history and memory of women artisans from Ilha Grande-PI, regarding the culture of bobbin lace as an intergenerational educational practice, transmitted through oral tradition. Based on the object in question, which consists of knowing how the history and memory of women lacemakers are translated into knowledge and actions based on an educational practice experienced outside the school context, this work proposes a study aimed at the analysis of these women's daily lives highlighting the relevance of their knowledge and practices, which can be known through the memory of these artisans. Thus, the construction of this work will be based on historical research, with an oral life history research methodology or thematic oral history research and will use the open interview technique to collect data that can assist in elucidating the following inquiries: How does the exchange of bobbin lace experiences happen? How does shared knowledge translate into education and culture? What aspects of the history of bobbin lace culture can be known from the memories of the lacemakers? How is bobbin lace know-how consolidated as an identity and cultural expression in Ilha Grande-PI? This work presents in the first chapter an approach to history and cultural memory, then it deals with education and the moving process of educational practice, it also highlights the distinction between formal, informal and non-formal education, and later, in the The third chapter deals with the action of the Ilhagrandense lacemaker in establishing a cultural identity. Some scholars were invited to dialogue during the theoretical foundation, such as Maihy and Holanda (2010), Halbwach (1990) Gomes (2004) and Gohn (2010) among other fundamental authors in the construction of knowledge in the scientific field.